Effect of Acupuncture on Blood Pressure and Metabolic Profile Among Patients With Essential Hypertension: Protocol of a Randomized Clinical Trial - Zhang, Pan; Chen, Yalan; Zhang, Furong; Pei, Hong; Sun, Mingsheng; Qu, Yuzhu; Chen, Jiyao; Du, Ting; He, Xiaoguo; Liang, Fanrong; Jia, Weiguo; Yang, Mingxiao (Frontiers in Cardiovascular Medicine, 2022)
Essential hypertension is a polygenic cardiovascular disease that is associated with maladaptive metabolic changes. Acupuncture as a non-pharmacologic intervention is used to lower blood pressure and improve metabolic dysfunction. However, such effects have not been clinically characterized. We will conduct a randomized clinical trial to evaluate the antihypertensive effect of acupuncture among patients with essential hypertension and determine the associated metabolic improvements. This study is a phase II, two-arm, randomized, sham-controlled trial (Trial registration: ChiCTR2100043737), in which biospecimens will be collected for metabolic profiling. A total of 64 patients with a clinical diagnosis of essential hypertension will be randomly assigned to either the acupuncture or the sham acupuncture group in a 1:1 ratio. All participants will receive 10 treatments over 4 weeks, with three sessions per week for the first 2 weeks and two sessions per week for the remaining weeks. The primary outcome is the change of the systolic and diastolic blood pressure measured by the 24-h ambulatory blood pressure monitoring from baseline to 4 weeks. Secondary outcomes include the circadian rhythm of blood pressure, sleep quality measured by the Insomnia Severity Index, cognitive function measured by the Montreal Cognitive Assessment, and others. Fasting blood serum and urine samples will be collected at baseline and 4 weeks for targeted and untargeted metabolomics analysis. We will use the mixed-effects model and other related bioinformatics approaches to analyze the clinical and metabolome data. This metabolomic-based trial will provide important clinical data regarding the efficacy of acupuncture for essential hypertension to better inform evidence-based care delivery for hypertension patients. Moreover, the findings will offer important insights into the mechanism of action of acupuncture for hypertension by revealing its effect on metabolism. The results of this study will be used to inform the design of a statistically powered, multicenter, randomized trial. We will publish the study findings in peer-reviewed journals. The ethical approval of this study has been reviewed and approved by the Sichuan Regional Ethics Review Committee on Traditional Chinese Medicine (ID: 2021KL-006). The outcomes of the trial will be disseminated through peer-reviewed publications.